2008
DOI: 10.1534/genetics.107.084236
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Social Effects to Heritable Variation in Finishing Traits of Domestic Pigs (Sus scrofa)

Abstract: Social interactions among individuals are ubiquitous both in animals and in plants, and in natural as well as domestic populations. These interactions affect both the direction and the magnitude of responses to selection and are a key factor in evolutionary success of species and in the design of breeding schemes in agriculture. At present, however, very little is known of the contribution of social effects to heritable variance in trait values. Here we present estimates of the direct and social genetic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(253 citation statements)
references
References 43 publications
17
228
6
2
Order By: Relevance
“…A farm may, for example, consist of units of 8-12 groups each, which introduces the risk of confounding environmental unit or unit  batch effects with IGEs, even when random group effects are included in the statistical model. Compared with a previous study (Bergsma et al, 2008), Bergsma et al (2013), for example, found substantially smaller IGEs in growth rate in domestic pigs due to an increase in the data set and a change in the statistical model.…”
Section: Estimating Igescontrasting
confidence: 73%
See 1 more Smart Citation
“…A farm may, for example, consist of units of 8-12 groups each, which introduces the risk of confounding environmental unit or unit  batch effects with IGEs, even when random group effects are included in the statistical model. Compared with a previous study (Bergsma et al, 2008), Bergsma et al (2013), for example, found substantially smaller IGEs in growth rate in domestic pigs due to an increase in the data set and a change in the statistical model.…”
Section: Estimating Igescontrasting
confidence: 73%
“…In populations consisting of small groups this covariance may be negative, which requires fitting a correlation between the residual terms of group mates (Bijma et al, 2007b). With large groups, the non-genetic covariance between group mates is likely positive, and can be accounted for by including a random groupeffect in the model (Arango et al, 2005;Bergsma et al, 2008). In populations of plants, including trees, spatial residual variance structures may be fitted to account for local environmental trend and for the non-genetic component of the indirect effect.…”
Section: Estimating Igesmentioning
confidence: 99%
“…Thus, genetic selection for resilience may benefit from selection on performance of the group rather than the individual (Muir 2005), especially where social stressors are likely to be a major cause of environmental stress to farm animals (Muir 1996;Bergsma et al 2008;Bolhuis et al 2009). Genetic models to disentangle direct and social effects have been developed by Bijma et al (2007).…”
Section: Group Performancementioning
confidence: 99%
“…Bijma et al (2007b) showed that non-genetic covariance among group mates can bias the estimates of genetic associative effects. Although we modelled social interactions differently, we fitted a random group effect to asses the magnitude of such non-genetic covariance in our analysis (see Bergsma et al 2008). The significance of the estimates of the SNPs effects from models [3] and [4] decreased only fractionally and did not affect the presented results at all.…”
Section: Social Interactionsmentioning
confidence: 99%